Examining the Use and Awareness of Educational Blogs among University Students - Farhana Khurshid (National University of Modern Languages (NUML), Islamabad, 2021)
Blogs are widely used in education since their emergence particularly in higher education. This research study investigated the use of educational blogs by students at university level. 100 male and female university students were the sample of this study. Data was collected through a questionnaire and focused group discussions. Descriptive statistics i.e., frequency and percentages, were calculated for the analysis of quantitative data and the qualitative data was analyzed through thematic analysis. The results of the study indicated that students used blogs to get educational ideas and communicate with other people. They used educational blogs and commented on relevant course related posts. In this way, students get knowledge of different subjects through blogs. Students and teachers also used educational blogs to get to know each other better by visiting and reading blogs. Educational blogs help teachers to teach and students to learn. It is suggested that at university and college level there should be workshops and awareness programs for the use of modern technology into education. Teachers should offer blogs related courses at university and college levels. This study also creates awareness among university students about the use of blogs for educational purposes.